2008
DOI: 10.1016/j.jtcvs.2008.07.053
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of a special acupuncture technique for pain after thoracotomy

Abstract: Objective To determine whether an acupuncture technique specially developed for a surgical oncology population (intervention) reduces pain or analgesic use after thoracotomy compared to a sham acupuncture technique (control). Methods One hundred and sixty two cancer patients undergoing thoracotomy were randomized to group A) preoperative implantation of small intradermal needles which were retained for 4 weeks or B) preoperative placement of sham needles at the same schedule. Numerical Rating Scale (NRS) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 16 publications
1
49
1
Order By: Relevance
“…Results demonstrated no significant difference between the intervention and the control groups at any of the follow-up periods (days 10, 30, 60, and 90). Pain scores were marginally higher in the intervention group (P = 0.9) and there were no significant differences for secondary end points including chronic pain, in-patient pain, and medication use in the hospital and following discharge [21].…”
Section: Post-surgical Cancer Painmentioning
confidence: 79%
“…Results demonstrated no significant difference between the intervention and the control groups at any of the follow-up periods (days 10, 30, 60, and 90). Pain scores were marginally higher in the intervention group (P = 0.9) and there were no significant differences for secondary end points including chronic pain, in-patient pain, and medication use in the hospital and following discharge [21].…”
Section: Post-surgical Cancer Painmentioning
confidence: 79%
“…18 Recently, several clinical trials have suggested the efficacy of acupuncture as an adjuvant method for postoperative analgesia 7,8,19 ; however, conflicting results have been reported also. [10][11][12] It is difficult to achieve a definitive conclusion from reviewing the literature; the main challenge is related to the language of publications (most papers have been published only in Chinese); furthermore, most studies reach only a low level of evidence, because of methodologic bias and lack of standardized procedures. In fact, several variants of the traditional method have been used to increase the acupuncture Table I .594…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Thus, several clinical trials evaluating the efficacy of acupuncture as adjuvant method for postoperative analgesia have been published. [7][8][9] Conflicting results have been reported, [10][11][12] probably owing to the heterogeneity in acupuncture techniques that may consistently vary according to the site, timing and type of stimulation. 4 In fact, electric, chemical, or physical stimulations have been also used in several studies to increase the effectiveness of the procedure.…”
mentioning
confidence: 99%
“…Electroacupuncture reduced pain and analgesic requirements significantly up to 72 h postoperatively. However, the effects in most of these trials were weak to moderate, and other studies could not detect any difference between intraoperative needling versus no additional treatment after laparoscopic hysterectomy and cholecystectomy [9], or perioperative treatment with small intradermal needles for 4 weeks in cancer patients undergoing thoracotomy [10 ]. Ten sessions of body needle acupuncture within 2 weeks in patients after total knee arthroplasty were not superior to sham acupuncture in terms of pain intensity, range of knee motion or ambulation time [11].…”
Section: Body Acupuncturementioning
confidence: 93%